The Role of the Government in Improving Tourism Services for the Jolotundo Temple - Nizar Fairus Hanim, Mukhammad; Sukmana, Hendra (Indonesian Journal of Public Policy Review, 2022)
This study uses a descriptive method intended to describe the role of government. The research subjects were the Head of Department of Culture, Youth, Sports and Tourism, the Head of the Regional Government, Perhutani, BPCB (Cultural Conservation Preservation Center). Data collection was obtained by interview, observation, and documentation methods. Data analysis was carried out by reducing data, presenting data, and drawing conclusions. The results of the study stated that the services provided were not optimal, as evidenced by the existence of a report from the BPCB (Cultural Conservation Preservation Center), the government's role in improving services had not been maximized. But there is a good side in improving services is to know and understand the duties and functions that are their responsibility, to carry out the role of government. The three trees around the Pertirtaan Jolotundo Temple are old and tall, they are afraid of rain and wind, but once every six months the government carries out tree mitigation. Fourth, there is heavy rain for more than two to three hours, it must be sterilized first, no visitors should come afraid of landslides. Fifth, when on the night of 1 Suro and Friday Legi people come to bathe in the booths using flowers and added fragrance oil, etc., it can affect the surface of the stone when it is cleaned it will peel off.